Compound heterozygous mutation of the SNX14 gene causes autosomal recessive spinocerebellar ataxia 20 - Shao, Yuqi; Yang, Saisai; Li, Jiafu; Cheng, Lin; Kang, Jiawei; Liu, Juan; Ma, Jianhong; Duan, Jie; Zhang, Yuanzhen (Frontiers in Genetics, 2024)
Genetic counseling was provided to a family with two children who were experiencing growth and developmental delays. The proband had prenatal ultrasound findings that included flattened frontal bones, increased interocular distance, widened bilateral cerebral sulci, and shortened long bones, which resulted in subsequent postnatal developmental delays. The older sister also displayed growth developmental delays and poor muscle tone. Whole exome sequencing (WES) was employed to identify compound heterozygous variants of c.712A>T (p.Arg238Ter) and .2744A>T (p.Gln915Leu) in the SNX14 gene in these two children. Both of them are novel missense variants that originate from the father and mother, respectively. Sanger sequencing confirmed this result. Following the guideline of the American College of Medical Genetics and Genomics (ACMG), the SNX14 c.712A>T (p.Arg238Ter) variant was predicted to be pathogenic (P), while the SNX14 c.2744A>T (p.Gln915Leu) variant was predicted to be a variant of uncertain significance (VUS).The structural analysis revealed that the c.2744A>T (p.Gln915Leu) variant may impact the stability of the SNX14 protein. In vitro experiments demonstrated that both the c.712A>T and c.2744A>T variants reduced SNX14 expression. The SNX14 gene c.712A>T (p.Arg238Ter) and c.2744A>T (p.Gln915Leu) were identified as the genetic causes of growth and developmental delay in two affected children. This conclusion was based on the clinical presentations of the children, structural analysis of the mutant protein, and in vitro experimental validation. This discovery expands the range of SNX14 gene variants and provides a foundation for genetic counseling and guidance for future pregnancies in the affected children's families.